Gender quotas and support for women in board elections - Marina Gertsberg; Johanna Mollerstrom; Michaela Pagel (Research Institute of Industrial Economics (IFN), 2022)
We study shareholder support for corporate board nominees before and after the 2018 California gender quota. Pre-quota, new female nominees received greater support than new male nominees, consistent with women being held to a higher standard. Post-quota, as the number of women increased, support for new (mandated) female nominees decreased to the same level of, but not lower than, the support that new male nominees enjoy. Still, share prices reacted negatively to the quota. We show that this reaction was concentrated in firms that did not turn over their least-supported male directors when adding women to comply with the quota.
Keywords: G30; G34; G38; J16; K38; 330; Board of directors; Gender quota; Regulation; Corporate Governance